A SYSTEM DYNAMICS MODEL TO ASSESS THE OPTIMAL NUMBER OF CREWS FOR CONDUCTING AIR CARGO OPERATIONS - Pozzi, R.; Noe, C.; Rossi, T. (European Scientific Journal, ESJ, 2013)
Notwithstanding the extensive studies involving the cargo terminal operations issues, a knowledge gap emerges. Literature has focused its research on the manpower assignment and the crew scheduling problems, whereas the determination of the cycle time of the activities to be performed, and, as a consequence, the job lead time, has been often neglected. Thus, filling such a gap is the goal of the present paper, which is aimed at developing and testing a model for defining the cycle time involved in air cargo terminal activities and the corresponding job lead time, in relation to both job characteristics and terminal resources. The causal diagram that depicts such relations is built and applied to a real process. Then, the assumptions based on the model are validated by means of data gathering and statistical analyses (ANOVA).